Subsídios para uma Leitura Desenvolvimental do Processo de Envelhecimento - Fonseca, António M. (2013)
Some theoretical approaches that look into human development as a coherent movement of systematic and organized changes in individual functioning and behavior are presented. These changes will demand a constant individual adaptation coping with transformations occurring in internal and external levels. Inspired by a contextualist paradigm of human development, the main aspects of four theories that try to explain the way how development occurs throughout human life are compared: ecological approach, developmental contextualism, theory of action and control, life-span developmental perspective. Some implications of common features of these theories are applied in what concerns the study of the process of aging, focusing the growing importance of the study of inter-individual differences in such process from the analysis of individual developmental pathways